Imipenem Resistance Mediated by blaOXA-913 Gene in Pseudomonas aeruginosa - Dong-Chan Moon; Abraham Fikru Mechesso; Hee-Young Kang; Su-Jeong Kim; Ji-Hyun Choi; Hyun-Ju Song; Soon-Seek Yoon; Suk-Kyung Lim (MDPI AG, 2021)
Treatment of infectious diseases caused by carbapenem-resistant Pseudomonas aeruginosa is becoming a greater challenge. This study aimed to identify the imipenem resistance mechanism in P. aeruginosa isolated from a dog. Minimum Inhibitory Concentration (MIC) was determined by the broth microdilution method according to the Clinical and Laboratory Standards Institute recommendations. We performed polymerase chain reaction and whole-genome sequencing to detect carbapenem resistance genes. Genomic DNA of P. aeruginosa K19PSE24 was sequenced via the combined analysis of 20-kb PacBio SMRTbell and PacBio RS II. Peptide-Peptide Nucleic Acid conjugates (P-PNAs) targeting the translation initiation region of blaOXA-913 were synthesized. The isolate (K19PSE24) was resistant to imipenem and piperacillin/tazobactam yet was susceptible to most of the tested antimicrobials. Whole-genome sequencing revealed that the K19PSE24 genome comprised a single contig amounting to 6,815,777 base pairs, with 65 tRNA and 12 rRNA genes. K19PSE24 belonged to sequence type 313 and carried the genes aph(3)-IIb, fosA, catB7, crpP, and blaOXA-913 (an allele deposited in GenBank but not described in the literature). K19PSE24 also carried genes encoding for virulence factors (exoenzyme T, exotoxin A, and elastase B) that are associated with adhesion, invasion, and tissue lysis. Nevertheless, we did not detect any of the previously reported carbapenem resistance genes. This is the first report of the blaOXA-913 gene in imipenem-resistant P. aeruginosa in the literature. Notably, no viable colonies were found after co-treatment with imipenem (2 µg/mL) and either of the P-PNAs (12.5 µM or 25 µM). The imipenem resistance in K19PSE24 was primarily due to blaOXA-913 gene carriage.